2014
DOI: 10.1080/00268976.2013.865809
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic investigation of the ionisation and dissociation decay dynamics of Rydberg states of NO

Abstract: Double-resonance spectroscopy has been employed to characterise the autoionising and predissociating Rydberg states of NO converging to the υ + = 0 and υ + = 1 levels of the X 1 + ground state of NO + . Below the lowest ionisation limit, we monitor the formation of the N( 2 D) predissociation product and observe a spectrum dominated by the p(N + = 0) series, with smaller contributions from the p(2) and f(2) series. Many of the lineshapes can be fit to a simple Fano line profile. Upon vibrational excitation, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Recently, we have reported on the lifetime of such states measured by electron-ion coincidence spectroscopy [7]. It has been demonstrated that electronically excited states play an important role in strong field phenomena, including ionization and molecular dissociation [8,9], electron wave packet interference, and high harmonic generation [10][11][12][13]. Many strong field phenomena in atoms and molecules are governed by electronic dynamics that are not only sensitive to the laser intensity but also to the waveform of the laser field [14].…”
mentioning
confidence: 99%
“…Recently, we have reported on the lifetime of such states measured by electron-ion coincidence spectroscopy [7]. It has been demonstrated that electronically excited states play an important role in strong field phenomena, including ionization and molecular dissociation [8,9], electron wave packet interference, and high harmonic generation [10][11][12][13]. Many strong field phenomena in atoms and molecules are governed by electronic dynamics that are not only sensitive to the laser intensity but also to the waveform of the laser field [14].…”
mentioning
confidence: 99%
“…Formation and destruction of such mesoscopic objects can be described by semiclassical and classical methods [5]. Recent experiments on high harmonic generation and electron wave packet interferometry indicate the important contribution of such excited states to different processes [6][7][8][9][10] including ionization and molecular dissociation processes [11][12][13][14]. However, detailed and quantitative information on the FFI following the interaction of femtosecond laser pulses with atoms and molecules appears to be scarce.…”
mentioning
confidence: 99%
“…44 Studies have been reported previously of the Δ v + ≠ 0 vibrational channel interactions in NO between Rydberg states in series converging to the v + = 1 series limit, and the v + = 0 continuum that give rise to autoionisation. 44,78 In the case of interest here these same vibrational channel interactions are seen to persist between states with v + = 0 and v + = 1 below both series limits.…”
Section: Resultsmentioning
confidence: 62%